Trade facilitation in developing countries - Chris Milner; Oliver Morrissey; Evious Zgovu (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2008)
Measures to actively facilitate trade are increasingly seen as essential to assist developing countries in expanding trade and benefiting from globalisation. Although often viewed as narrowly concerned with the ease and speed of Customs procedures, even greater trade cost reductions and trade and welfare benefits may be reaped from a broader view of trade facilitation (TF) that incorporates transportation, distribution and communication issues. A number of TF reforms are particularly beneficial: improving procedures, especially Customs clearance; introducing automation and use of information technology; reducing excessive documentation requirements; addressing lack of transparency in import and export requirements; addressing lack of modernisation of and cooperation between Customs and other government agencies. The review identifies the types of TF reforms that could address these problems and deliver a return in terms of increased revenue collection efficiency, reductions in trade costs and promotion of greater regional cooperation (at least in Customs and transport, especially as many TF measures are appropriate for inclusion in regional integration agreements).
Keywords: F14; F15; F17; 330; Trade Facilitation; Regional Integration; Außenwirtschaft; Handelsabkommen; Außenhandelsliberalisierung; Regionalismus; Entwicklungsländer